1998
DOI: 10.1038/sj.bmt.1701186
|View full text |Cite
|
Sign up to set email alerts
|

Autologous stem cell transplantation (ASCT) for poor prognostic Hodgkin’s disease (HD): comparative results with two CBV regimens and importance of disease status at transplant

Abstract: Clinical outcome of 47 consecutive patients with advanced HD who underwent ASCT in our Department was analyzed retrospectively. Median age was 28 years (28 males and 19 females). At transplant, 15 (32%) patients were in CR (five in first CR after two chemotherapy regimens and 10 in second CR), eight (17%) in PR (seven without a prior CR), 22 (51%) had relapsing disease (19 with sensitive relapse) and two had primary refractory disease. The CVB regimen with two different schedules was used: 22 (47%) patients re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 21 publications
(77 reference statements)
0
18
0
Order By: Relevance
“…Some of these subjects may not proceed to transplantation because of intercurrent medical problems associated with multiple attempts to induce remission. This inherent selection bias may explain, in part, the less favorable results in untested relapse patients, reported by groups such as Sweetenham and colleagues 34 and Arranz et al 40 Thus, superior results for second complete remission patients may not be the result of a beneficial effect of re-induction therapy but rather from identification of good prognosis patients.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Some of these subjects may not proceed to transplantation because of intercurrent medical problems associated with multiple attempts to induce remission. This inherent selection bias may explain, in part, the less favorable results in untested relapse patients, reported by groups such as Sweetenham and colleagues 34 and Arranz et al 40 Thus, superior results for second complete remission patients may not be the result of a beneficial effect of re-induction therapy but rather from identification of good prognosis patients.…”
Section: Discussionmentioning
confidence: 87%
“…Factors predicting poor outcome in prior studies of autotransplants for relapsed or refractory Hodgkin's disease a Interval from end-of-therapy until relapse Ͻ12 months (34,36,39) у1 extra-nodal disease site at relapse (34,35,39,40) Abnormal ECOG performance status (38,43,46,49,51,52) a Resistant relapse (38,42,47) a B symptoms at relapse (39,48,49) Bulk disease at transplant (33,40,41,44,49,53) Female gender (33) Exposure to many chemotherapeutic regimens prior to transplant (33,35,46,47,51,52) Elevated serum LDH at transplant (50) Relapse in previous radiation field (44) Disseminated lung or marrow disease at relapse (49) a Factors reported specifically in first relapse/second complete remission patients. Numbers in parenthesis refer to study cited.…”
Section: Tablementioning
confidence: 99%
“…6,14,15 In the current series of patients, high-dose therapy with stem cell rescue was useful for patients who did not achieve complete remission after conventional therapy. Both patients transplanted in partial remission and those transplanted in relapse, attained CR.…”
Section: Discussionmentioning
confidence: 99%
“…We did not find a significant difference in EFS rates according to disease status at the time of ASCT, probably because of the small size of this group, since status at transplantation has been proven to be a significant prognostic factor in larger series of adult patients. 6,14,15,17 No randomized studies comparing the effectiveness of ASCT vs standard chemotherapy in relapsed children with HD have been reported. Despite the fact that the follow-up time in our series of patients is not yet very long, the overall outcome is encouraging with an overall survival of 0.95 and EFS rate of 0.62.…”
Section: Discussionmentioning
confidence: 99%
“…Predicted OS at 8 years (median follow-up 28 months) favored the BEAM regimen over the CEB (CBV) regimen (58 vs 40%). Arranz et al, 18 on univariate analysis, found that absence of extranodal disease and CR status at transplant were associated with better PFS. In our study, more patients in the CEB group were in CR at the time of ASCT than in the BEAM group, and more CEB patients had a history of prior CR than BEAM; however, more patients who received CEB had extranodal disease than patients who received BEAM (55 vs 20%, Po0.05).…”
Section: Discussionmentioning
confidence: 99%